2011
DOI: 10.1002/adsc.201100349
|View full text |Cite
|
Sign up to set email alerts
|

Iron‐Facilitated Iodine‐Mediated Electrophilic Annulation of N,N‐Dimethyl‐2‐alkynylanilines with Disulfides or Diselenides

Abstract: An efficient synthesis of N-methyl-3-chalcogeno-indoles has been developed via iodine-mediated electrophilic annulation reactions of 2-alkynyl-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
68
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 139 publications
(72 citation statements)
references
References 28 publications
2
68
0
1
Order By: Relevance
“…On the basis of the present results and our previous work, [12] a plausible mechanism was outlined as shown in Scheme 3. The electrophilic annulation still works in the absence of FeCl 3 (entry 20 in Table 1) and the iodocyclization product could not be detected (Scheme 2).…”
supporting
confidence: 68%
See 1 more Smart Citation
“…On the basis of the present results and our previous work, [12] a plausible mechanism was outlined as shown in Scheme 3. The electrophilic annulation still works in the absence of FeCl 3 (entry 20 in Table 1) and the iodocyclization product could not be detected (Scheme 2).…”
supporting
confidence: 68%
“…Low yields were also observed using PdA C H T U N G T R E N N U N G (OAc) 2 or CuA C H T U N G T R E N N U N G (OAc) 2 as catalyst (entries 2 and 3). During the examination of solvent effects, we found that the cyclization reaction nearly did not proceed in DCE, MeCN or DMSO (entries [11][12][13]. Treatment of substrate 1a with 1,2-diphenyldisulfane, iodine and 10 mol% of FeCl 3 in CH 3 NO 2 at 120 8C afforded the desired prod-Scheme 1.…”
mentioning
confidence: 99%
“…In this pathway, thiophenol (1a) is initially oxidized to 1,2-diphenyldisulfane (4a) under the standard conditions. The reaction of 4a with I 2 forms an electrophilic species PhSI (I), 11 which is then attacked by 3-phenylpropiolate (2a) to yield intermediate II, intramolecular arylation of which provides III. This is followed by the loss of HI to form 3a.…”
Section: Letter Syn Lettmentioning
confidence: 99%
“…14 Recently, Li and co-workers developed a simple and efficient transition metalpromoted electrophilic annulation method for the synthesis of 3-chalcogenoindoles [Eqn (2)]. 15 However, transition metalbased protocols usually have inherent limitations, including moisture sensitivity, costly metal catalysts and environmental toxicity. Therefore, there is still a need for developing a direct and metal-free method to synthesise 3-sulfenylindoles.…”
mentioning
confidence: 99%
“…Here, we report the metal-free synthesis of 3-sulfenylindoles via an iodinemediated electrophilic cyclisation of 2-alkynylanilines with disulfides [Eqn (3), Scheme 1]. [15][16][17] * Correspondent. E-mail: taoliming2005@yahoo.com.cn…”
mentioning
confidence: 99%